Understanding Digital Responsibilities - Lizzie Coles-Kemp; Mark Burdon (Bristol University Press, 2026)
Available open access digitally under CC-BY-NC-ND licence. How can we make the digital world safer, more responsible and accountable? This innovative book offers an original framework for understanding digital responsibility, blending insights from law, technology and policy. Through a series of case studies showcasing work from early career researchers, it highlights the diverse groups, values and governance challenges shaping digital environments across jurisdictions. From crafting effective policies to designing ethical digital products, this book equips policy makers, practitioners and academics with the tools to minimise harm and enhance accountability and responsibility in the digital age. This is a vital resource for navigating the complexities of digital responsibility in a pluralistic, globalised world.